2019
DOI: 10.1177/0018720819874544
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Tracking Metrics Predict Perceived Workload in Robotic Surgical Skills Training

Abstract: Objective: The aim of this study is to assess the relationship between eye-tracking measures and perceived workload in robotic surgical tasks. Background: Robotic techniques provide improved dexterity, stereoscopic vision, and ergonomic control system over laparoscopic surgery, but the complexity of the interfaces and operations may pose new challenges to surgeons and compromise patient safety. Limited studies have objectively quantified workload and its impact on performance in robotic surgery. Although not y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 101 publications
(129 reference statements)
2
73
1
Order By: Relevance
“…Workload can be defined with self-rating techniques, where a subject fills a questionnaire about his/her personal experience about the task workload. It is naturally a subjective technique, however, there are works in the literature which studied both subjective workload measurements and objective non-technical skill assessment metrics [ 32 , 40 ], or objective physiological parameters [ 30 , 34 , 41 , 42 , 43 , 44 , 45 , 46 ]. Workload measurements do not only help to assess the personal workload index, but also to define the main stressors and disturbing factors in surgery in general, furthermore, to provide personal training for novices as well.…”
Section: Technical Approaches For Non-technical Skill and Mental Workload Assessment In Ramismentioning
confidence: 99%
See 3 more Smart Citations
“…Workload can be defined with self-rating techniques, where a subject fills a questionnaire about his/her personal experience about the task workload. It is naturally a subjective technique, however, there are works in the literature which studied both subjective workload measurements and objective non-technical skill assessment metrics [ 32 , 40 ], or objective physiological parameters [ 30 , 34 , 41 , 42 , 43 , 44 , 45 , 46 ]. Workload measurements do not only help to assess the personal workload index, but also to define the main stressors and disturbing factors in surgery in general, furthermore, to provide personal training for novices as well.…”
Section: Technical Approaches For Non-technical Skill and Mental Workload Assessment In Ramismentioning
confidence: 99%
“…NASA-TLX is a widely used technique for workload measurement in aviation, military and healthcare. NASA-TLX can be found in traditional MIS mental workload estimation [ 48 , 49 , 50 , 51 , 52 ], and employed in the case of surgical robotics workload assessment as well [ 8 , 32 , 34 , 40 , 41 , 43 , 45 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. There are additional mental workload assessment techniques that are not originally created for surgery, and used in workload assessment for RAMIS.…”
Section: Technical Approaches For Non-technical Skill and Mental Workload Assessment In Ramismentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have also shown that after an unpleasant-stimulus, emotions were indexed by eye-blink startle, and left-sided frontal EEG activation occurred 36 . Visual metrics have also been proposed for detection of human physiological changes including mental fatigue 37 , cognition and cognitive development 38 , mental workload evaluation 39,40 , stress level in students 41 , threat-related emotional facial expressions in infancy 42 , shared attention for virtual agent 43 , and emotional arousal and autonomic activation 44 .…”
Section: Introductionmentioning
confidence: 99%